TRPC Channels in the Physiology and Pathophysiology of the Renal Tubular System: What Do We Know? - Englisch, Colya N.; Paulsen, Friedrich; Tschernig, Thomas (International Journal of Molecular Sciences, 2023)
The study of transient receptor potential (TRP) channels has dramatically increased during the past few years. TRP channels function as sensors and effectors in the cellular adaptation to environmental changes. Here, we review literature investigating the physiological and pathophysiological roles of TRPC channels in the renal tubular system with a focus on TRPC3 and TRPC6. TRPC3 plays a key role in Ca2+ homeostasis and is involved in transcellular Ca2+ reabsorption in the proximal tubule and the collecting duct. TRPC3 also conveys the osmosensitivity of principal cells of the collecting duct and is implicated in vasopressin-induced membrane translocation of AQP-2. Autosomal dominant polycystic kidney disease (ADPKD) can often be attributed to mutations of the PKD2 gene. TRPC3 is supposed to have a detrimental role in ADPKD-like conditions. The tubule-specific physiological functions of TRPC6 have not yet been entirely elucidated. Its pathophysiological role in ischemia-reperfusion injuries is a subject of debate. However, TRPC6 seems to be involved in tumorigenesis of renal cell carcinoma. In summary, TRPC channels are relevant in multiples conditions of the renal tubular system. There is a need to further elucidate their pathophysiology to better understand certain renal disorders and ultimately create new therapeutic targets to improve patient care.
CRIS-Team Scopus Importer:2023-01-20
Keywords: autosomal dominant polycystic kidney disease; ischemic injury; kidney; renal carcinoma; renal tubular system; transient receptor potential; TRPC3; TRPC6